2009
DOI: 10.3201/eid1505.081084
|View full text |Cite
|
Sign up to set email alerts
|

Possible Seasonality ofClostridium difficilein Retail Meat, Canada

Abstract: We previously reported Clostridium difficile in 20% of retail meat in Canada, which raised concerns about potential foodborne transmissibility. Here, we studied the genetic diversity of C. difficile in retail meats, using a broad Canadian sampling infrastructure and 3 culture methods. We found 6.1% prevalence and indications of possible seasonality (highest prevalence in winter).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 11 publications
(9 reference statements)
10
84
1
2
Order By: Relevance
“…The prevalence of C. difficile found in this study is similar to that found in other recent Canadian studies (11,12) but is lower than that reported in a study from the United States (17). This should not be taken as an indication of regional variation in contamination because of the different methods that were used and the different products that were tested.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The prevalence of C. difficile found in this study is similar to that found in other recent Canadian studies (11,12) but is lower than that reported in a study from the United States (17). This should not be taken as an indication of regional variation in contamination because of the different methods that were used and the different products that were tested.…”
Section: Discussionsupporting
confidence: 72%
“…Initial studies have reported isolation of C. difficile from 4.6 to 45% of retail meat samples (11,12,17). However, all studies have used broth enrichment protocols, which could detect very low spore numbers and provide no information about the number of organisms present in a sample.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to hospitalacquired infection, C. difficile disease with community acquisition and community onset was associated with a wide variety of genotypes (Table 6). Community-acquired disease may be associated with the ingestion of C. difficile spores in meat or other foods (Rodriguez-Palacios et al, 2009;Visser et al, 2012), which would be expected to be heterogeneous, and this may explain the wide variety of genotypes identified. Martin et al (2008) found no association between NAP1/ribotype 027 and age, gender and inpatient/outpatient status.…”
Section: Discussionmentioning
confidence: 99%
“…While early studies conducted in North America reported a much higher contamination rate than elsewhere (Rupnik and Songer 2010), recent studies show the situation to be similar to other countries (Table 4). Rodriguez-Palacios et al (2009), noting an increased recovery of the bacterium from ground beef and chops in winter in Canada, suggested a seasonal component in C. difficile contamination in meats, and also hypothesised a possible epidemiological connection between the prevalence of C. difficile in food animals, some foods and humans .…”
Section: Prevalence and Food Products Concernedmentioning
confidence: 99%